PERANCANGAN MOTIF TEKSTIL UNTUK KEMEJA KASUAL DENGAN SUMBER IDE TOKOH WAYANG BIMA - Ikhsani, Trinurseto (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2024)
This artistic research is carried out to develop motif designs with digital print techniques which will be directed by exploring visual motifs with the source of the Bima puppet character idea to be developed towards more creative and innovative designs.This design uses a design approach that goes through three main processes, namely; the process of exploration, termination, and extraction (Palgunadi. 2007).The results of this development succeeded in creating 6 designs with an illustrative and modern visual style. The application of this development is directed at casual shirts for men with an age range of 17-25 years, taking into account the selection of appropriate colors and compositions so as to produce creative and innovative products that have characteristics and updates in terms of design.This development resulted in a new design display that bridged textile motifs with today's casual shirt products. By using digital processing techniques, this development can produce designs that consider more realistic and imaginative visual results but do not eliminate the philosophical essence of the motif itself